COMBINED TREATMENT OF A LARGE AGGRESSIVE CENTRAL GIANT CELL GRANULOMA - Mahmut Koparal; Hilal Alan; K.serkan Ağaçayak; İ.halil Erdoğdu; Belgin Gulsun (Cumhuriyet University, 2017)
Central giant cell tumours are rare, accounting for less than 7% of all jaw tumours. These tumours are usually observed in women, occur most often in the mandible, and are more common in the second decade of life. Treatment consists of local removal, partial resection, or total resection. In this case, a 32-year-old female patient presented in our clinic with pain in the anterior mandible. No cervical lymphadenopathy was detected upon physical examination. No ulceration was observed during the intraoral examination, but sensitivity was found in the vestibular area. However, no sensation loss in any teeth or in the lips was detected. This case report presents a 32-year-old female patient with central giant cell tumour causing extensive bone loss in the mandible base that was treated with partial resection.